Strategi Pemberdayaan Masyarakat Pesisir Secara Terpadu Di Kota Semarang (Studi Kasus Di Kelurahan Mangunharjo) - Eka Putri Arviyanthi; Margaretha Suryaningsih; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In coastal resource management is the key issue is still very large number of coastal communities whose income is below the average standard specified and is still dealing with health issues, lack of clean water, abrasion. The decline in environmental quality and carrying capacity. Limited facilities and infrastructure, as well as accessibility and the level of funding available include programs for sustainable resource management. Implementation of coordination or cooperation and optimizing the utilization of existing coastal resources is a solution to the problem of coastal community empowerment. However, until now the condition of the community empowerment can not be run with the maximum. The purpose of this study is to analyze the conditions of empowerment, analyzing environmental strategies, identify constraints, identify the enabling and inhibiting factors, identify key success factors, and provide a recommendation strategy for empowerment of coastal communities in Mangunharjo empowerment by analyzing the condition of coastal communities with environmental strategic SWOT analysis . Were then carried out the identification of strategic issues which further tested the Litmus Test as a way to define strategic issues existing empowerment of coastal communities. In this qualitative study using snowball sampling technique (snowball sampling). Method of data collection used in this study is the in-depth interview techniques and selecting the speakers with a purposive system. From the results obtained, the conclusions obtained are the condition of coastal resources that exist in the Village Mangunharjo constantly increasing. A key success factor for coordination and cooperation strategies for the empowerment of coastal communities, namely the implementation of coordination or cooperation fatherly mentoring and development of processed marine and administrative training includes training on the operation of the network use the Internet, as well as preparing the budget allocation for the program to be executed